Understanding the pattern and volume of various orthopaedic disorders observed at a tertiary care hospital, before and during the COVID-19 pandemic - Rathod, Girish; Borole, Pushkar; Shetty, Chandan; Raut, Nitin; Britto, Namrata; Gawali, Vijaykumar (International Journal of Research in Orthopaedics, 2022)
Background: The COVID-19 pandemic has lead to a huge loss of life and disruption of lifestyle. The pandemic has also led to disruption in the health sector, as significant changes in the pattern of hospital admissions, medical care and variations in disorders have been observed especially in the orthopaedics department. To assess the change in pattern and volume of trauma in our region, we evaluated data from our center for the pandemic period and compared it with the previous years’ data (pre-pandemic period). Methods: Comparison of orthopaedic in-patient records was carried out of the pre-pandemic and during the COVID-19 period, to assess the effect of COVID-19 on the orthopaedic in-patient load and prevailing diseases. Medical records of the patients were analyzed and the data collected were subjected to statistical analysis using IBM SPSS software version 1.0. Results: Significant reduction in patient load was observed during the pandemic period. Cases of various types of fractures were observed to be high in number, followed by arthritis. The only disorder that was observed to be highly prevalent in both the periods is proximal femur fractures. Conclusions: A high variation was observed in both the volume and nature of trauma presentations during the COVID-19 lockdown. A significant decrease in overall admissions was observed, this could be related to the period of societal restrictions and nationwide lockdown.